Immune Checkpoint Inhibitors for Advanced Melanoma: Experience at a Single Institution in Taiwan - Wu, Chiao-En; Yang, Chan-Keng; Peng, Meng-Ting; Huang, Pei-Wei; Lin, Yu-Fen; Cheng, Chi-Yuan; Chang, Yao-Yu; Chen, Huan-Wu; Hsieh, Jia-Juan; Chang, John Wen-Cheng (Frontiers in Oncology, 2020)
Background: Immune checkpoint inhibitors (ICIs) have significantly changed the current approach to cancer treatment. Although the use of ICIs has become the standard of care for advanced melanoma, reports of ICI use among Asian populations with melanoma are limited. Therefore, we conducted this retrospective study to assess the efficacy and safety of ICI use in Taiwanese patients. Patients: Patients with histologically confirmed melanoma treated with ICIs at Linkou Chang Gung Memorial Hospital from January 2014 to July 2019 were retrospectively reviewed. Univariant and multivariant analyses were performed to identify possible prognostic factors. Results: Among 80 patients, 45 were treatment-naïve (56.3%) and 35 received prior systemic drugs other than ICIs. Regarding treatment regimens, patients were treated with ipilimumab (n=9), nivolumab (n=33), pembrolizumab (n=16), or combination drugs (n=22). Nine patients achieved either a complete (n=2) or partial (n=7) response and 13 patients were stable, with a resulting response rate of 11.3% and disease control rate of 27.5%. As of the last follow-up in January 2020, patients treated with combination drugs had longer median progression-free survival (PFS) of 5.6 (95% confidence interval [CI]: 1.6-9.6) months than nivolumab (2.9 months, 95% CI: 1.9-3.9 months), pembrolizumab (3.2 months, 95% CI: 2.6-3.8 months), and ipilimumab (2.6 months, 95% CI: 2.4-2.8 months) (p=0.011). No significant differences in overall survival (OS) among the four regimens (p=0.891) were noted. In the multivariate analysis, combination treatment, disease control, and performance < 1 were independent prognostic factors for PFS. Liver metastases and no disease control were independent unfavorable prognostic factors for OS. The most common factor was skin toxicity (45%), followed by endocrine toxicity (18.8%). Patients undergoing combination treatment experienced more frequent and serious adverse events than patients undergoing monotherapy. Conclusion: ICIs demonstrated efficacy and safety in Taiwanese patients with melanoma. Combination treatment showed the greatest efficacy, but this was also accompanied by greater toxicity among the 4 regimens. In addition, we identified important prognostic factors, such as liver metastases, performance status, and tumor response, for both PFS and OS. These findings could provide physicians with more information to justify clinical outcomes observed in Asian patients with advanced melanoma.